FENOMENA KEKERASAN GENDER DALAM KULTUR PATRIARKHI : KAJIAN SOSIOLOGI SASTRA - Sylvie Meiliana (Jurnal Ilmu dan Budaya, 2018)
The  aim of this research is to reveal the gender violence reflected in patriarchal culture. Gender violence is a global phenomenon and mostly women become the victims. This research is focussing on gender violence towards American women reflected in an American literary work. As a literary research, the data source of this research is an American novel, Journey written by an American woman writer, Danielle Steel. This descriptive qualitative research applied content analysis technique that is performed by taking a flow models, namely data reduction, data presentation, and drawing conclusions. The findings are as follows. First, the novel Journey written by Danielle Steel reveals three types of gender violence, they are physical, psychological, and sexual abuse. Second, as a literary theory, sociology of literature can be applied to portray gender violence as a social phenomenon in patriarchal culture  through a literary work.